The complete software project manager : mastering technology from planning to launch and beyond - Murray, Anna, 1966- (Hoboken, New Jersey : Wiley, 2016)
Your answer to the software project management gap The Complete Software Project Manager: From Planning to Launch and Beyond addresses an interesting problem experienced by today's project managers: they are often leading software projects, but have no background in technology. To close this gap in experience and help you improve your software project management skills, this essential text covers key topics, including: how to understand software development and why it is so difficult, how to plan a project, choose technology platforms, and develop project specifications, how to staff a project, how to develop a budget, test software development progress, and troubleshoot problems, and what to do when it all goes wrong. Real-life examples, hints, and management tools help you apply these new ideas, and lists of red flags, danger signals, and things to avoid at all costs assist in keeping your project on track. Companies have, due to the nature of the competitive environment, been somewhat forced to adopt new technologies. Oftentimes, the professionals leading the development of these technologies do not have any experience in the tech field-and this can cause problems. To improve efficiency and effectiveness, this groundbreaking book offers guidance to professionals who need a crash course in software project management.-Review the basics of software project management, and dig into the more complicated topics that guide you in developing an effective management approach -Avoid common pitfalls by perusing red flags, danger signals, and things to avoid at all costs -Leverage practical roadmaps, charts, and step-by-step processes -Explore real-world examples to see effective software project management in action The Complete Software Project Manager: From Planning to Launch and Beyond is a fundamental resource for professionals who are leading software projects but do not have a background in technology.
Getting All the Roles CoveredReal-World Examples for Role-Blending; Professionals and Personalities; Insource or Outsource: Whether to Staff Roles with Internal People or Get Outside Help; The Myth that Insourcing Programming Is Better; Inexperience with Projects; How Knowledge Goes Stale; Outsourced Teams; When to Use Internal or External Teams; Roles Easiest to Outsource; Roles "in the Middle"; Roles that Are Usually Internal; Vendors and Hiring External Resources; Some Tech-Types to Avoid: Dot Communists and Shamans; The Shamans; Boundaries, Responsibilities, and Driving in Your Lane.
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Computer software -- Development; Software engineering -- Management; COMPUTERS -- Software Development & Engineering -- General; Computer software -- Development; Software engineering -- Management